Islam Syariat: Reproduksi Salafiyah Ideologis di Indonesia - Zain, Muhammad Fuad; Basit, Abdul (Jurnal Syariah dan Hukum Komparatif, 2024)
Haedar Nashir's book on Islam Syariat: Reproduksi Salafiyah Ideologis di Indonesia is a fairly thick research comprising 604 pages. This book analyzes the Islamic movement that fights to implement Islamic Sharia in the context of state institutions carried out by MMI, HTI, and KPPSI. In this book, researchers combine literature and field research with emic data. The ideological thread of the Sharia Islamic Movement (Formalist) is a documentation of the "creed of Islamic solutions" integrated with Islamism/ Kaffah Islam. The culmination of formalization was the appearance of the seven magic sentences of the Jakarta Charter at the 2000 MPR-RI Meeting. At the same time, the largest mass organizations in Indonesia, represented by Muhammadiyah and Nahdlatul Ulama, were outside the movement, even refusing or not supporting the fight for the Jakarta Charter. In an academic context, the revitalization of fundamentalist, literal, and scriptural Islam contains harmful elements in the context of statehood and the plurality of the nation. Furthermore, the ideological conflict of Islam in Indonesia must be understood that Indonesia is not Islam in the face of the West or Arabization but must present Moderate Islam, which offers an alternative path, so that it does not give rise to a new flow of conversion to Islam to other religions which are seen as providing more comfort in religion, rather than being in Islam which is formalist and has an ideological face.